23.6k views
5 votes
Given that (3x+2) is a factor of 3x^3+bx^2-3x-2. find the value of b?

1 Answer

11 votes

Answer:


b = 2.

Explanation:

By the factor theorem, if a monomial of the form
(x - a) is a factor of the polynomial
(3\, x^(3) + b\, x^(2) - 3\, x - 2), then substituting in
x = a would set this polynomial to
0.

Notice that in the factor theorem, the coefficient of
x in
(x - a) is
1, and the sign in front of the constant
a is a minus sign. Rewrite the given factor
(3\, x + 2) in this form to find the value of
a\!:


\begin{aligned}& (3\, x + 2) \\ =\; & 3\, (x + (2/3)) \\ =\; & 3\, (x - \underbrace{(-2/3)}_(a)) \end{aligned}.

Thus,
x = (-2/3) should set the polynomial
(3\, x^(3) + b\, x^(2) - 3\, x - 2) to
0:


\begin{aligned} & (3\, x^(3) + b\, x^(2) - 3\, x - 2) \\ =\; & 3* (-2/3)^(3) + b* (-2/3)^(2) - 3 * (-2/3) - 2 \\ =\; & -3* (2/3)^(3) + b* (2/3)^(2) + 3 * (2/3) - 2 \\ =\; & -(8)/(9) + (4\, b)/(9) + 2 - 2 \\ =\; & (-8 + 4\, b)/(9)\end{aligned}.

Set this expression to
0 and solve for
b:


\displaystyle (-8 + 4\, b)/(9) = 0.


b = 2.

User Daniel Werner
by
6.4k points